El poema "Ad statuam puellae" del Cardenal Viseu y la “Vergine della fontana” de Villa Giulia en Roma - Pino González, Eduardo del, 1966- (Ágora : estudos clássicos em debate, 2016)
In this paper we provide the critical edition, first translation and commentary of the poem entitled Ad statuam puellae, written by the Portuguese humanist Miguel da Silva. The commentary allows us to establish a connection between the text and the “Fontana della Vergine” in Villa Giulia at Rome and particularly with one of its statues. On the other hand, the poem reinforces one of the hypotheses about the general conception of that architectural complex